Targeting CYP2J2 to Enhance the Anti-Glioma Efficacy of Cannabinoid Receptor 2 Stimulation by Inhibiting the Pro-Angiogenesis Function of M2 Microglia - Lei, Xuejiao; Chen, Xuezhu; Quan, Yulian; Tao, Yihao; Li, Junlong (Frontiers in Oncology, 2020)
Enhancing the therapeutic efficacy of anti-tumor drugs is essential for the management of cancer. Although cannabinoid receptor 2 (CB2R) stimulation exerts anti-tumor action in glioma cells via regulating cellular proliferation, differentiation or apoptosis, selective CB2R agonist alone does not achieve a satisfactory therapeutic outcome. Herein, we aimed to test the possible strategy for enhancing the anti-glioma efficacy of JWH133, a selective CB2R agonist. In this study, immunofluorescence and QRT-PCR were used to investigate microglia polarization. Tumor growth was monitored via bioluminescent imaging using IVIS Spectrum system. The angiogenesis of human brain microvascular endothelial cells (HBMECs) was detected by Tube Formation Assay. QRT-PCR was used to investigate CYP2J2 and 11,12-epoxyeicosatrienoic acid (11,12-EET) expression. Our results demonstrated that administration of JWH133 significantly promoted microglial M2 polarization in vivo and in vitro. The medium supernatant of JWH133-induced microglia but not JWH133 directly facilitated angiogenesis of HBMECs. CYP2J2 expression and 11,12-EET release in the supernatant of JWH133-induced M2 microglia were significantly upregulated. Treatment with 11,12-EET prompted angiogenesis of HBMECs and the growth of glioma. CYP2J2 knockdown restrained the release of 11,12-EET and significantly enhanced the antitumor effect of JWH133 on glioma. This study uncovered that targeting CYP2J2 may be a beneficial strategy to enhance the anti-glioma efficacy of JWH133 by inhibiting the pro-angiogenesis function of M2 microglia.